Pharmacokinetics of a single dose of rimantadine in young adults and children. - Anderson, E L (1987)
Single doses of rimantadine were given to children and young adults to evaluate the safety and pharmacokinetics of this antiviral compound. The half-life of rimantadine in young adults was 27.7 +/- 4.9 h for tablets and 27.8 +/- 8.0 h for syrup preparations. A total of 10 children, 5 to 8 years old, received a syrup preparation of rimantadine. The half-life of rimantadine in children was 24.8 +/- 9.4 h. A single dose of rimantadine was well tolerated in young adults and children.